2021
DOI: 10.1016/j.isci.2021.103352
|View full text |Cite
|
Sign up to set email alerts
|

Ancient genome analyses shed light on kinship organization and mating practice of Late Neolithic society in China

Abstract: Anthropology began in the late nineteenth century with an emphasis on kinship as a key factor in human evolution. From the 1960s, archaeologists attempted increasingly sophisticated ways of reconstructing prehistoric kinship but ancient DNA analysis has transformed the field, making it possible, to directly examine kin relations from human skeletal remains. Here, we retrieved genomic data from four Late Neolithic individuals in central China associated with the Late Neolithic Longshan culture. We provide direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…In China, such a study was only carried out in a Late Neolithic archaeological site associated with the Longshan culture. This study revealed that the Longshan household was not organized through nuclear family but rather extended family and further provided direct evidence of consanguineous mating practices in Longshan society (Ning et al, 2021). Here, kinship analysis was used to determine the burial customs in the historical period of northern China.…”
Section: Introductionmentioning
confidence: 98%
“…In China, such a study was only carried out in a Late Neolithic archaeological site associated with the Longshan culture. This study revealed that the Longshan household was not organized through nuclear family but rather extended family and further provided direct evidence of consanguineous mating practices in Longshan society (Ning et al, 2021). Here, kinship analysis was used to determine the burial customs in the historical period of northern China.…”
Section: Introductionmentioning
confidence: 98%
“…The use of paleogenomes for inferring genetic kin relations in ancient human populations is growing at an accelerating pace. These studies have unraveled diverse types of social relations of past human societies, from the composition of households [1,2] or burial treatment of mass murder victims [3] to matrilineal [4] or patrilineal traditions studied in graves [5][6][7][8]. However, determining kinship degree using single nucleotide polymorphism (SNP) data from low-coverage genomes is fraught with difficulties, mainly arising from data scarcity.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, researchers must be aware of the potential effects of the nature of past and recent population contact situations, and their dynamics, as well as the dynamics of the non-linguistic variables under focus. Ideally, work in genetics in these regards will also shed further light on the problems, and solutions, involved in studying language change throughout time, since genetics enables us to reconstruct detailed human genealogies and populations movements in the past (Sikora et al, 2017 ; Skoglund and Mathieson, 2018 ; Bose et al, 2021 ; Ning et al, 2021 ; Serrano et al, 2021 ; Barbieri et al, 2022 ). For instance, family pedigrees and mating practices can be confidently inferred from ancient DNA and later used to estimate the nature of social networks, which together with other factors, like population number or forms of sociopolitical organization, seem to play a key role in shaping language features, as discussed above.…”
mentioning
confidence: 99%